DETERMINANTS OF THE QUALITY OF VILLAGE FINANCIAL STATEMENTS AND THE IMPLEMENTATION OF SISKEUDes AS A MEDIATION VARIABLES - Trisnawati, Rina; Achyani, Fatchan; Ulifiati, Nur (Universitas Muhammadiyah Surakarta, 2020)
This study aims to analyze the factors affecting the quality of village financial statements using SISKEUDes (village financial system application), which had been implemented in villages in the Tegal Regency as an intervening variable. These factors encompassed human resource competence, management commitment, system user training, and data quality. This study’s population was all users of the SISKEUDes system in villages throughout Tegal Regency, totaling 281 villages. The sampling technique employed was the convenience sampling method. Respondents were the SISKEUDes application users who were present at the SISKEUDes 2.0 software extension program. The data were obtained by distributing questionnaires to 281 SISKEUDes users, but only 218 could be processed into data. The data analysis then utilized SEM-PLS with Smart PLS 3.0 software. The results showed that human resource competence, top management commitment, and user training directly had a significant positive effect on the quality of village financial statements. Besides, the variable of SISKEUDes implementation served as a mediation variable for system user training on the quality of village financial statements.